2019
DOI: 10.7189/jogh.09.010804
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement and mobilisation of local resources to support integrated Community Case Management of childhood illnesses in Niger State, Nigeria

Abstract: Background Despite strong evidence of integrated community case management (iCCM) of childhood illnesses being a proven intervention for reducing childhood morbidity and mortality, sustainability remains a challenge in most settings. Community ownership and contribution are important factors in sustainability. The purpose of this study was to document the process and scale achieved for community engagement and mobilisation to foster ownership, service uptake and sustainability of iCCM activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 18 publications
(24 reference statements)
1
31
0
Order By: Relevance
“…In the future, qualitative inquiry would give further insight into these findings. The finding of CE in the form of a monetary contribution suggests the sustainability of water filters as also found in Cha et al (2017) and Alegbeleye et al (2019).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…In the future, qualitative inquiry would give further insight into these findings. The finding of CE in the form of a monetary contribution suggests the sustainability of water filters as also found in Cha et al (2017) and Alegbeleye et al (2019).…”
Section: Resultssupporting
confidence: 56%
“…Specifically, the investigators found that community‐trained volunteers successfully increased donations and improved use of local resources. Authors reported that raising donations were “signs of community ownership, which, if encouraged, will enhance sustainability of the project” (Alegbeleye et al., 2019, p. 8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 All these different CE approaches have contributed to improved awareness, early detection of cases and improved access and wider community acceptance of malaria prevention and treatment in the afore-mentioned countries. [16][17][18][19] This paper describes the protocol for a scoping review that aims to describe CE approaches targeting the prevention, control or elimination of malaria that have been/or are being implemented by countries.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 16 In Nigeria, integrated community case management has been used to detect and treat malaria cases in remote areas using trained local community health workers, minimising travel time and the cost for patients. 17 Similarly, in Cameroon and Cambodia, local volunteers and village malaria workers have been used to conduct proactive and reactive case detection in communities to prevent transmission, 11 18 while the Interactive Malaria Awareness Program in South Africa has successfully used home-based care workers to form local-level partnerships and to also educate communities on malaria prevention and control. 19 All these different CE approaches have contributed to improved awareness, early detection of cases and improved access and wider community acceptance of malaria prevention and treatment in the afore-mentioned countries.…”
Section: Introductionmentioning
confidence: 99%